Associações entre as cargas parasitárias com o estresse oxidativo e alterações clínico-laboratoriais na leishmaniose visceral canina - Torrecilha, Rafaela Beatriz Pintor [UNESP] (2015)
Canine visceral leishmaniasis (CVL) is a zoonosis of great epidemiological relevance. Infected dogs usually present nonspecific clinical and laboratory alterations that hampers the diagnosis of the disease in routine screening, and the use of techniques with higher sensitivity and sensibility, such as the detection of the parasite by polymerase chain reaction (PCR), are often necessary. Among the nonspecific alterations, anemia is one of the most frequently found, but the mechanism underlying its occurrence is still under dispute. Oxidative stress, the imbalance between oxidants and antioxidants, has been recently incriminated as one of the possible triggers of anemia in CVL. Here, we investigated the putative relationships between parasite load and markers of oxidative stress and hematologic, biochemical and clinical alterations in dogs naturally infected with Leishmania spp. Markers of oxidative stress included albumin, uric acid, bilirubin, total antioxidant capacity (TAC), total oxidant capacity (TOC), oxidative stress index (TOC/TAC) and serum and packed red cells Thiobarbituric acid reactive substances (TBARS). Additional laboratory analysis included complete blood count (CBC) and biochemical profile. Observation of clinical alterations was scored as present or absent. Quantitative PCR (qPCR) of tissue samples of skin, conjunctiva, whole blood and packed white cells was used to estimate tissue-specific parasite load. In order to represent the total parasite load (i.e., the parasitism across different analyzed tissues), we applied a principal components analysis to the matrix of tissue-specific qPCR results to create a single synthetic variable that captures the information content present in the four different original variables. We found no significant associations between hematologic parameters and parasite load, and previously reported alterations such as sample hemolysis or icteric serum were not observed. However, significant differences